61.4k views
5 votes
Factor completely 3x4 − 48. 3(x2 − 4)(x2 + 4) 3(x − 2)(x + 2)(x + 2)(x + 2) 3(x − 2)(x + 2)(x2 + 4) 3(x − 2)(x + 2)(x2 − 4)

User Mridula
by
5.8k points

2 Answers

3 votes

Answer:

3 (x-2) (x+2) (x^2+4)

Explanation:

User Terry Djony
by
6.0k points
2 votes

Answer:

3 (x-2) (x+2) (x^2+4)

Explanation:

3x^4 − 48

Factor out a 3

3(x^4 -16)

Inside the parentheses is the difference of squares (a^2 - b^2) = (a-b) (a+b)

where a = x^2 and b = 4

3 (x^2-4) (x^2+4)

Inside the first parentheses is the difference of squares where a = x and b=2

3 (x-2) (x+2) (x^2+4)

User Blhsing
by
5.8k points